Blends in Modern Literary Arabic within the naming processes - Y. S. Ayvazyan (Vestnik MGIMO-Universiteta)
This paper is dedicated to the analysis of morphological, syntactic and typological characteristics of blends in Modern Literary Arabic in the course of sociopolitical terminology within the naming processes.